2020
DOI: 10.1002/cssc.202000032
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Photoelectrochemical Catalysis: Solar‐Induced Green Synthesis of Organic Molecules

Abstract: Scheme8.Mechanism for the PEC CÀHa mination resulting in the conventionallydominating para configurationand proposed mechanism for the formation of the ortho product, owingtoh ydrogen bonding (dashedl ines) stabilizing the intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 31 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…Diverse (hetero)aryl halides were studied first, and results showed that the C-H arylation reaction could be carried out by (hetero)aryl bromides, and even (hetero)aryl chlorides with moderate to excellent yields after 7.5-9 h (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Many functional groups that may be sensitive to strong reducing conditions, such as ketone (3)(4)(5), aldehyde (6), ester (7-8 and 12), cyano (13)(14)(15)(16), and sulfonamide (34) groups exhibited good tolerance. The derivatives bearing acetyl at the different positions of the benzene ring (3-5) showed good activity.…”
Section: Scope Of Reductive Functionalization Of Aryl Halidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Diverse (hetero)aryl halides were studied first, and results showed that the C-H arylation reaction could be carried out by (hetero)aryl bromides, and even (hetero)aryl chlorides with moderate to excellent yields after 7.5-9 h (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Many functional groups that may be sensitive to strong reducing conditions, such as ketone (3)(4)(5), aldehyde (6), ester (7-8 and 12), cyano (13)(14)(15)(16), and sulfonamide (34) groups exhibited good tolerance. The derivatives bearing acetyl at the different positions of the benzene ring (3-5) showed good activity.…”
Section: Scope Of Reductive Functionalization Of Aryl Halidesmentioning
confidence: 99%
“…The derivatives bearing acetyl at the different positions of the benzene ring (3-5) showed good activity. When the aromatic ring was substituted with two functional groups, the reaction took place efficiently with a yield of 96% (15). Aside from halogenated aromatic hydrocarbons, halogenated heteroaromatics (e.g., 3-bromoquinoline 9, 5-bromopyrimidine 11) were efficiently arylated in moderate to excellent yields (9-11 and 16-17).…”
Section: Scope Of Reductive Functionalization Of Aryl Halidesmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Likewise, Ahmed and co-workers summarized some of the latest research efforts in using photoelectrochemical cells. 22 Protected amides commonly react with alkynes, providing simple isoquinolones, being catalyzed by Ni, Ru, Rh, and Co, among others. [23][24][25][26][27] Likewise, Tang and co-workers proposed the first double-electrocatalytic organometallic C−H activation with amides 1 and alkynes 2 for the synthesis of polycyclic isoquinolinones 3 (Scheme 1).…”
Section: C-heteroatom and C-c Bond Formationmentioning
confidence: 99%
“…Thus, the reader is referred to a number of earlier review articles that are also relevant to these themes . Beyond the scope of this review are photoelectrodes, and other practical aspects of electrochemistry, which have been addressed in recent tutorial reviews …”
Section: Introductionmentioning
confidence: 99%